Errors in interpretation of neck levels in postoperative pathological specimens. Issue 3 (April 2017) - Varley, I.; Howe, T.E.; Hunter, K.; Smith, A.T.
Abstract: Accurate orientation of pathological specimens is of fundamental importance, and specimens that are divided postoperatively may be misinterpreted. We asked surgeons and pathologists to identify boundaries between nodal levels on a clinical photograph of a neck dissection specimen. Few participants were able to identify the boundaries between levels accurately, with several important errors where a marked level contained none of the relevant anatomical tissue. Most errors were in level I, and the number decreased towards level IV. Errors were made by both pathologists and surgeons. The boundaries of level IIA were consistently overestimated, which may have implications for previous studies that evaluated patterns of nodal spread.